CHARACTERISTICS OF SONG TRANSLATION AND ENGLISH-VIETNAMESE SONG TRANSLATIONS - Quynh, Doan Thuy (VNU Journal of Foreign Studies; Vol 35 No 2DO - 10.25073/2525-2445/vnufs.4351, 2019)
In this article, we review some major theories related to translation and song translation. The song translation strategies, which are introduced by Peter Low, are as follows: translation, adaptation and replacement (text). He has also introduced the “Pentathlon Principle”, which comprises of rhyme, rhythm, naturalness, singability, and sense to song translation. The Pentathlon Principle is illustrated by our analysis of 3 Vietnamese versions of English songs. The results show that all the tunes are maintained as the original, while the semantically translated version ensures the same meaning, content, characters as well as the whole story as the original. By contrast, the adapted version only retains the theme, the plot and the characters. For the last one, the lyrics are completely novel – the translator creates a new story over the original tune. The study results also show that all three versions observe the “Pentathlon Principle”, and singability and rhyme come high on the list of priorities.